2005
DOI: 10.4315/0362-028x-68.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Escherichia coli O157:H7 in Inoculated and Naturally Colonized Feedlot Cattle and Their Environment

Abstract: On-farm methods of monitoring Escherichia coli O157:H7 were assessed in 30 experimentally inoculated steers housed in four pens over a 12-week period and in 202,878 naturally colonized feedlot cattle housed in 1,160 pens on four commercial Alberta feedlots over a 1-year period. In the challenge study, yearling steers were experimentally inoculated with 10(10) CFU of a four-strain mixture of nalidixic acid-resistant E. coli O157:H7. After inoculation, shedding of E. coli O157:H7 was monitored weekly by collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
4
26
1
1
Order By: Relevance
“…Our data contribute to the growing body of evidence indicating that E. coli O157:H7 persists in cattle populations. More specifically, along with several previous studies (6,43,45,48,51), our study supports the conclusion that a given population of feedlot cattle appears to be colonized by a single predominant strain and a few closely related strains. The predominant PFGE subtype in our study was disseminated into each animal pen, was found on each sample collection date, and was shed by each PS animal on at least two consecutive sample collection dates.…”
Section: Vol 75 2009 Persistence Of E Coli O157:h7 In Feedlot Cattsupporting
confidence: 78%
“…Our data contribute to the growing body of evidence indicating that E. coli O157:H7 persists in cattle populations. More specifically, along with several previous studies (6,43,45,48,51), our study supports the conclusion that a given population of feedlot cattle appears to be colonized by a single predominant strain and a few closely related strains. The predominant PFGE subtype in our study was disseminated into each animal pen, was found on each sample collection date, and was shed by each PS animal on at least two consecutive sample collection dates.…”
Section: Vol 75 2009 Persistence Of E Coli O157:h7 In Feedlot Cattsupporting
confidence: 78%
“…These alterations were associated with a quantifiable neutrophilic response. The microscopic examination was made in animals shedding bacterial numbers similar to those animals considered super-shedders in field studies (10,22,34). Similar lesions have been reported in weaned calves 4 days postchallenge (7).…”
Section: Discussionmentioning
confidence: 95%
“…The seasonality of the incidence of E. coli O157:H7 in petting zoo animals, coupled with the increase in E. coli O157:H7 associated with food-borne illness during the summer months, suggests that environmental replication plays a key role in the epidemiology of infections [42, 43]. …”
Section: Discussionmentioning
confidence: 99%